Gene expression of human endometrial L-selectin ligand in relation to the phases of the natural menstrual cycle - Tsung-Hsuan Lai (Nature Portfolio, 2018)
Abstract This study investigates peptide components of L-selectin ligand (LSL) and their gene expressions in human endometrium during the natural menstrual cycle. We recruited 41 endometrial samples from reproductive-aged women with leiomyoma and undergoing hysterectomy and 11 endometrial samples from menopausal women as controls. Immunohistochemistry revealed strong MECA-79 expression from the early through the mid-secretory phase and low expression in menopausal endometrium. Five peptide components of LSL were detected in reproductive and menopausal endometrium by one-step quantitative RT-PCR: podocalyxin, endomucin, nepmucin, GlyCAM-1, and CD34. Endomucin differed significantly between the proliferative and early-secretory phases. CHST2 and CHST4 genes (which are involved in the generation of LSL epitopes) were expressed without significant differences among phases. The gene expression of progesterone receptor decreased from the proliferative to the late-secretory phase, and the difference was significant. However, estrogen receptor α expression showed stability among phases. The significant expression of endomucin between the proliferative and early-secretory phases might play a vital role in endometrial receptivity. Further studies are needed to investigate the factors that regulate the expression of endomucin and other LSL peptide components in different phases of the menstrual cycle.